IMPLEMENTASI PROBLEM BASED LEARNING DENGAN PENDEKATAN NEUROSAINS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP - Wachufyah, Putri Isu; Sulistyaningrum, Heny (FKIP Unirow Tuban, 2022)
This research is motivated by the fact that there is still a lack of understanding of students in the material presented, resulting in students having difficulty solving mathematical problems. The purpose of this study was to test whether there was a significant effect on the implementation of problem based learning with a neuroscience approach on the mathematical problem solving abilities of eighth grade students of junior high school. This research is a quantitative study using a pre-test-post-test control group design experiment. The research population was class VIII SMP Negeri 5 Tuban, with the research sample being class VIII B students as the control class and class VIII F as the experimental class and selected using cluster random sampling technique. Data collection techniques used are tests and observations. The data analysis technique used is t-test. The results of the study indicate that there is a significant effect on the implementation of the implementation of problem based learning with a neuroscience approach to problem solving abilities.